Upaya Eradikasi Stunting Berbasis Social-Ecological Approach di Kelurahan Untia Kota Makassar - Harisa, Akbar; Hastuti, Hastuti; Majid, Abdul; Malasari, Silvia; Permana, Andi Fajrin; Abdullah, Meutiah Mutmainnah; Hardianty, Nita; Dzauqy, Amrun; Sari, Dewi Novita; Yodang, Yodang (Jurnal Abdimas Kesehatan (JAK), 2024)
Kampung Nelayan Untia as a Family Planning (KB) village. It  was established in 2016, with most of its residents working as fishermen. Based on the data collected, this village has several cases of stunting. The solution offered is to provide education and counseling in the form of stunting material. The implementation of the Community Service Activity "Efforts to Eradicate Stunting Based on a Social-Ecological Approach in Untia Village, Makassar City" aims to provide knowledge and skills to the Untia community about stunting prevention. The results of this activity showed enthusiasm from the participants, which also proved an increase in participants' knowledge. The Community Service Team hopes that the local government can continue to follow up on the stunting prevention program to reduce the number of stunting cases in the Untia community.